Comparison of Tissue Heat Balance- and Thermal Dissipation-Derived Sap Flow Measurements in Ring-Porous Oaks and a Pine - Renninger, Heidi J.; Schafer, Karina V. (Frontiers in Plant Science, 2012)
Sap flow measurements have become integral in many physiological and ecological investigations. A number of methods are used to estimate sap flow rates in trees, but probably the most popular is the heat dissipation method (Granier) because of its affordability, relatively low power consumption and ease of use. However, there have been questions about the use of this method in ring-porous species and whether individual species and site calibrations are needed. We made concurrent measurements of sap flow rates using heat dissipation sensors and the heat balance method (Čermák) in two oak species (Quercus prinus Willd. and Quercus velutina Lam.) and one pine species (Pinus echinata Mill.). We also made concurrent measurements of sap flow rates using both 1-cm long and 2-cm long Granier-style heat dissipation sensors in both oak species. We found that both the heat dissipation and heat balance systems tended to match well in the pine individual, but sap flow rates were underestimated by 2-cm long heat dissipation sensors in five individuals of the two ring-porous oak species. Underestimations of 20-35% occurred in Q. prinus even when a “Clearwater” correction was applied to account for the shallowness of the sapwood depth relative to the sensor length and flow rates were underestimated by up to 50% in Q. velutina. Two-cm long heat dissipation sensors also underestimated flow rates compared with 1-cm long sensors in Q. prinus, but only at large flow rates. When 2-cm long sensor data in Q. prinus were scaled using the regression with 1-cm long data, daily flow rates matched well with the rates measured by the heat balance system. Daily plot-level transpiration estimated using heat dissipation sap flow rates was about 15% lower than those estimated by the heat balance method at the highest flow rates. Therefore, these results suggest that 1-cm long sensors are appropriate in species with shallow sapwood, however more corrections may be necessary in ring-porous species.